Identify The Elements and Principles of David Lauer's Design in The Vessel Building - Wijaya, Antonius Sachio Troy; Roosandriantini, Josephine; Yuniardi, Dimas (RUAS, 2025)
This research examines the application of David Lauer's design elements and principles in The Vessel by Thomas Heatherwick, an iconic contemporary architectural structure located in Hudson Yards, New York. As a landmark of modern urban design, The Vessel combines aesthetic innovation with functional interactivity, making it an intriguing subject for analyzing how basic design theory is implemented in contemporary architecture. The study aims to identify and evaluate the use of design elements (such as line, shape, texture, and space) and design principles (including balance, rhythm, proportion, and hierarchy) in The Vessel, as well as their contribution to the unique spatial experience and visual impact. The research method employs a descriptive approach through visual observation and literature review. The findings reveal that The Vessel successfully integrates Lauer's design principles to create a harmonious, dynamic, and engaging structure, reaffirming the importance of design fundamentals that prioritize aesthetics and functionality in contemporary architecture.